POLITIK HUKUM PENANAMAN MODAL ASING SETELAH BERLAKUNYA UNDANG-UNDANG PENANAMAN MODAL 2007 DAN IMPLIKASINYA TERHADAP PENGUSAHA KECIL - abdullah, sayidin (FIAT JUSTISIA, 2014)
abstractThis research aims to describe the choice of law of foreign investment after the entry into force of the Law on Investment and Its Implications for Small Entrepreneurs. By using a normative approach and secondary data, it can be concluded that the regulation and law on the matter of foreign investment in the Investment Law of 2007 do not distinguish between domestic investors and foreign investors. Equal treatment between domestic investors and foreign investors; providing facilities for foreign investors, among others: exemptions or tax relief, repatriation of capital, facilities of permit, and the submission of disputes to international arbitration body. However, the liberalization principles of international trade and foreign investment are contrary to the principles of economic democracy on Article 33 of 1945 Constitution, which requires the fulfillment of the fundamental rights of every individual without exception, while the terms of trade liberalization contained in the WTO are based on the idea of capitalism that restrict the basic rights and only those who are able to compete can enjoy the benefits of international trade provisions of the WTO. It means that Investment Law economically and legally does not provide adequate protection for small entrepreneurs.Â Keywords: Legal Politics, Investment and Implications.